An Economical, Agri-Compliant and Environmentally Sustainable ‘Sponge Culture’ Method for Large-Scale Production of Actinopigments from soil Actinomycetes - Gupta, Hajra AS.; Pande, Ashlesha; Sanklecha, Dhwani; Tuscano, Holden; Tankaria, Anjaly; Pinto, Andrea (International Journal of Scientific Research in Biological Sciences, 2020)
Actinomycetes are potent producers of color and antimicrobial pigments, having found applications in the pharmaceutical and food sectors. Unfortunately, industrial fermentation of actinopigments is not carried out on large-scale due to obstacles faced in their culture, product harvest, and expenditure. Additionally, the use of rice, wheat bran, and other food-based culture substrates limit the exploration of actinopigments only to the laboratory. To overcome such hurdles, we describe here a novel ?sponge culture? method for the culture of Actinomycetes and extraction of color pigments. In the sponge culture method, a polyurethane sponge was used as an inert substrate for attachment and propagation of the isolates in the form of a modified submerged fermentation technique. Three soil Streptomyces spp., brown, black and yellow, identified from mycelial morphology and biochemical tests, were inoculated in sponge culture and rice bed culture. Actinopigments, extracted in organic solvents, were obtained in solution by sponge culture, and as a fine powder in rice bed culture. Pigments extracted from the sponge culture method were read in a UV visible spectrophotometer to record their λmax. The two culture-extraction methods were compared based on ease of extraction, expenditure, efficiency, being environment, and agriculture friendly. The sponge culture method proved not only superior to rice culture but also economical. With this method, the industrialization of actinopigments appears practical, profitable, and consumer-friendly. This technique wins the approval of agriculture society and environmentalists, discouraging the use of food-based substrates and promoting the recycling of plastic sponge for a cleaner environment